Molten pool flow behavior and influencing factors in electron beam selective melting of IN738 superalloy - Zhang, Yihui; Fang, Xuewei; Zhang, Wannian; Guo, Wenhua; Wang, Zhixiang; Zhao, Jiyuan (Frontiers in Materials, 2023)
Electron beam selective melting (EBSM) has emerged as a promising technology for additive manufacturing (AM) of superalloys. However, the understanding of molten pool flow behavior and the factors influencing forming quality in EBSM remains limited. This study aims to address this gap by developing a comprehensive multi-physics model for the EBSM process, which analyzes the effects of fluid flow, environmental conditions, and process parameters. To establish the powder bed model and track the solid-liquid free surface, the discrete element method (DEM) and volume of fluid (VOF) method are employed, respectively. The results reveal that the molten pool exhibits a conduction mode characterized by a large width-to-depth ratio driven by the Marangoni effect. Internal vortices cause the molten pool to expand even after the scan ends. The ambient pressure, in comparison to the preheat temperature, has a significant impact on vapor recoil and consequently affects the surface quality of the molten pool. Moreover, a large hatch distance results in cracks and porous morphological features on the surface of the samples. These findings demonstrate the effectiveness of numerical simulations in providing detailed insights into the EBSM process of the IN738 superalloy material.